Simbiosis Mutualisme: Hukum Islam dan Perbankan Syariah - Arifin, Asriadi; Abubakar, Achmad; Haddade, Hasyim; Ramadhani, Syamsinar (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
Studies that formulate sharia banking and Islamic law in force in Indonesia have never been studied before, so researchers are currently giving the term symbiosis of mutualism because between sharia banking and Islamic law provide mutual benefits. This library research is a research whose data comes from library sources, namely literature review through library research. The main reference sources in research are adapted from various experts who talk about banking, including: Thamrin Abdullah & Francis Tantri in his book "Banks and Financial Institutions”, Herry Sutanto & Khaerul Umam in his book "Islamic Bank Marketing Management", Muhammad, in his book "Sharia Bank Management” Thamrin Abdullah and Francis Tantri in his book "Banks and Financial Institutions, and Muhammad in his book "Sharia Financing Management”. In addition, it also uses secondary references that are adapted by researchers from various relevant scientific studies. The results show that the principles of Islamic law governing the operations of Islamic banks ethically and morally help Islamic banks to minimize financial risks and ensure fair and balanced transactions. By adhering to these foundations, Islamic banking can avoid bankruptcy risk, maintain its financial stability, and generate halal and blessed profits. Therefore, Islamic law is very important for the sustainability of Islamic banking as a financial instrument that focuses on the application of Islamic law and principles.